Intercellular adhesion molecule-1 expression and serum levels as markers of pre-clinical atherosclerosis in polycystic ovary syndrome - Nearmeen M. Rashad; Amal S. El-Shal; Hala G. Abomandour; Amr Mostafa Kamel Aboelfath; Mohamed el sayed Rafeek; Mohammad Samir Badr; Ayman E. Ali; Mohammed S. Yousef; Maha Abdelhamid Fathy; Mustafa taha Abdelfattah Sharaf el din (BMC, 2019)
Abstract Background Polycystic ovary syndrome (PCOS) is a common reproductive endocrine disorder characterized by obesity, hyperandrogenism, and insulin resistance. Intercellular adhesion molecule-1 (ICAM-1) is a proinflammatory and proatherogenic cytokine which is associated with atherosclerosis, insulin resistance, and cardiovascular disease (CVD). The pathogenesis of PCOS is not precisely known. Thus, the purpose of this study was to investigate the potential role of ICAM-1 expression and serum ICAM-1 concentrations in pathogenesis of PCOS. Moreover, we aimed to evaluate the possible relationship between ICAM-1 gene expression with carotid intima-media thickness as well as clinic-morphological features of PCOS. Methods This case control study enrolled 180 patients with PCOS and 120 controls groups and they were stratified according to their fasting plasma glucose (FPG) into three subgroups; normal glucose tolerance (NGT) [n = 75], those with impaired glucose tolerance (IGT) [n = 65], and 40 patients with type 2 diabetes mellitus (T2DM). Circulating ICAM-1 expression levels were determined by real time polymerase chain reaction (RT-PCR). Serum ICAM-1 concentrations were measured using enzyme-linked immunosorbent assay (ELISA). Results Our results revealed that PCOS patients had higher values of ICAM-1expression and serum levels. Among PCOS patients, T2DM patients had the highest values of ICAM-1 expression and serum levels compared to IGT and NGT subgroups. The ICAM-1 expression and serum levels were significantly positive correlated with cardiovascular risk and PCOS phenotypes. Linear regression test showed that HOMA-IR was the main predictors of serum ICAM-1 levels in PCOS. Receiver operating characteristic curve (ROC) analysis revealed that, the power of ICAM-1 expression levels was higher than serum ICAM-1 in diagnosis of PCOS and in differentiating T2DM from IGT and NGT subgroups. Interestingly, combination of both ICAM-1 expression and serum levels improved the diagnostic role of serum ICAM-1. Conclusion ICAM-1 expression and serum levels were higher in women with PCOS compared to control group also, there was a strong independent association between higher ICAM-1 expression and serum levels with cardiovascular risks in PCOS group.